(Y+4)+(2y)+(3y-1)=19/5

Simple and best practice solution for (Y+4)+(2y)+(3y-1)=19/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (Y+4)+(2y)+(3y-1)=19/5 equation:



(+4)+(2Y)+(3Y-1)=19/5
We move all terms to the left:
(+4)+(2Y)+(3Y-1)-(19/5)=0
We add all the numbers together, and all the variables
2Y+(3Y-1)+4-(+19/5)=0
We get rid of parentheses
2Y+3Y-1+4-19/5=0
We multiply all the terms by the denominator
2Y*5+3Y*5-19-1*5+4*5=0
We add all the numbers together, and all the variables
2Y*5+3Y*5-4=0
Wy multiply elements
10Y+15Y-4=0
We add all the numbers together, and all the variables
25Y-4=0
We move all terms containing Y to the left, all other terms to the right
25Y=4
Y=4/25
Y=4/25

See similar equations:

| 5m+1=7m-5,m=3,-1 | | 3+6e=15 | | 12+3p=30 | | 2(1-2x)/2-2x=-2/5+4(2-3x)/3 | | Y=0.02x | | 5(x+15)=3x-19 | | 28(5x+5)+82(2x+8)=180 | | 28(5x+5)=82(2x+8) | | 2z–15=30 | | x+2x+x+15+x+15-27=360 | | 5x=327 | | 28(2x+8)=82(5x-4) | | X+5x+28=70 | | 4t-3=5(t=4) | | 6x=27−3x | | 4x+5x-27=54 | | 11/12-1/6q+5/6=1/3 | | N/3+n/5=40 | | -3-b=-9 | | 6x+4x=330 | | 5x+3=-4x-6 | | 4(3j+(-4))=-9 | | (Y+3)+y=25 | | 4k=33 | | -10+x/4=-14 | | -3-b=9 | | 11z=50 | | 14d=33 | | -9+k/5=-5 | | (18+2x)-3=45 | | -8-2b=30 | | -2b+3=-21 |

Equations solver categories